RESEARCH OF A TANK-CONTAINER STRENGTH OF IMPROVED CONSTRUCTION USING THE COMPUTER SIMULATION OF OPERATING CONDITIONS - Lovskaya, A. O.; Fomin, O. V.; Okorokov, A. M.; Melnychuk, O. M. (Science and Transport Progress, 2015)
Purpose. This article highlights the сoverage of the results and characteristics of computer research of tank-container construction strength in operation that was improved by using round pipes as supporting constructions. Methodology. To achieve this aim, operation conditions of the typical tank-container construction were investigated. To study the strength of the tank-container in operation the spatial geometric model was constructed. The maximum equivalent stresses that occur in its supporting structures under the action of the most adverse operating conditions load were defined. Calculations were carried out using the finite element method. It was found that the margin of safety of the standard design container is about 2. For the metal content contraction of the tank-container it is proposed the improvement of its supporting construction by replacing round pipes instead of square pipes, which are used in typical design (providing in terms of durability and operational reliability). Findings. The improved supporting structure of the tank-container for transporting the petroleum products was developed. For the optimal design of its frame optimality research were conducted on the criterion if minimum material consumption. Originality. A model of strength tank-container which provides the possibility to determine the equivalent stresses in its supporting structure by encountering as the most unfavorable case of load was offered. The improved supporting structure of a tank-container using simulation optimization was developed. The improved construction of a tank-container is designed for all types of loads specified in the regulations. Practical value. The results of strength calculation showed that the tension of an improved supporting construction of a tank-container in the main modes of operating does not exceed the allowable values. Technical and economic feasibility of the proposed engineering solutions to the supporting construction showed that it was possible to make substantial economic effect during their production. The obtained results prove that the introduction of round pipes as the supporting constructions of freight cars and other means of transport engineering is a promising direction of a scientific research.